2018
DOI: 10.1007/s00253-018-9022-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, codon-optimized gene expression, and bioactivity assessment of two novel fungal immunomodulatory proteins from Ganoderma applanatum in Pichia

Abstract: Fungal immunomodulatory proteins (FIPs) have been identified from a series of fungi, especially in Ganoderma species. However, little is known about the FIPs from G. applanatum. In this study, two novel FIP genes, termed as FIP-gap1 and FIP-gap2, were cloned from G. applanatum, characterized and functionally expressed after codon optimization in Pichia pastoris GS115. Results showed that FIP-gap1 and FIP-gap2 comprised 342-bp encoding peptides of 113 amino acids, which shared a high homology with other Ganoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…And the IC 50 value of another FIP, FIP-sch3 ( Stachybotrys chartarum ), was 10.80 μg/mL [29]. Besides, the cytotoxicity of rFIP-gaps towards A549 and Hela cells in current study was accordant with those in previous reports with very similar IC 50 values [35].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…And the IC 50 value of another FIP, FIP-sch3 ( Stachybotrys chartarum ), was 10.80 μg/mL [29]. Besides, the cytotoxicity of rFIP-gaps towards A549 and Hela cells in current study was accordant with those in previous reports with very similar IC 50 values [35].…”
Section: Discussionsupporting
confidence: 85%
“…Ever since the first FIP, known as LZ-8 or FIP-glu, was isolated from the mycelia of G. lucidum by Kino et al in last century [24], more than fifteen FIPs have been identified from different fungi to date [2531]. Nine of those FIPs are from Ganoderma species including LZ-8 (FIP-glu, G. lucidum ), LZ-9 ( G. lucidum ), FIP-gts ( G. tsugae ), FIP-gja ( G. japonicum ), FIP-gsi ( G. sinense ), FIP-gmi ( G. microsporum ), FIP-gas ( G. astum ), FIP-gbo ( G. boninense ), FIP-gat ( G. atrum ), FIP-gap1 and FIP-gap2 (both from G. applanatum ) [3235]. The FIPs consist of 110–114 amino acids with molecular weights of 12–13 kDa, which are rich in Asp and Val but poor in His, Cys and Met.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIP-glu can enhance the transcription of IL-2, IL-3, IL-4, IFN-g, and TNF-a (60). FIP-gts (Ganoderma tsugae) can induce cytokine secretion, and FIP-gaps enhances IL-2 and IFN-g release from mouse lymphocytes (23). However, FIP-gmi from Ganoderma microsporum exhibits the effect of down regulation of TNF-a (28).…”
Section: Discussionmentioning
confidence: 99%
“…The first FIP, designated as FIP-glu (LZ-8), was isolated from Ganoderma lucidum (Kino et al, 1989). Until now, FIPs have been isolated and identified from several fungi, such as Flammulina velutipes (FIP-fve) (Ko, Hsu, Lin, Kao, & Lin, 1995), Volvariella volvacea (FIP-vvo) (Hsu, Hsu CI, Kao, & Lin, 1997), Auricularia polytricha (FIP-app) (Sheu, Chien, Chien, Chen, & Chin, 2004), Ganoderma microsporum (FIP-gmi) (Wu et al, 2007), Ganoderma sinense (FIP-gsi) (Zhou, Xie, Hong, & Li, 2009), Poria cocos (FIP-pcp) (Chang, Yeh, & Sheu, 2009), Trametes versicolor (FIP-tvc) (Li, Wen, Liu, Zhou, & Chen, 2012), Nectria haematococca (FIP-nha) (Bastiaan-Net et al, 2013), Ganoderma lucidum (LZ-9) (Bastiaan-Net et al, 2013), Postia placenta (FIP-ppl) (Li, Shi, Ding, Nie, & Tang, 2015), Ganoderma atrum (FIP-gat) (Xu et al, 2016), Chroogomphis rutilus (FIP-cru) (Lin et al, 2016), Dichomitus squalens (FIP-dsq2) (Li et al, 2017), Ganoderma applanatum (FIP-gap) (Zhou et al, 2018), and Lentinus tigrinus (FIP-lti) (Gao et al, 2019). A protein family called FIPs was composed of these proteins (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%